Evaluation of the effectiveness of a comprehensive care plan to reduce hospital acquired complications in an Australian hospital: protocol for a mixed-method preimplementation and postimplementation study - Rebecca Leigh Jessup; Maree Glynn; Michael Kirk; Liz McKeown (BMJ Open)
Introduction A new healthcare standard (Standard 5: Comprehensive Care) has been introduced by the Australian Commission on Safety and Quality in Healthcare. Standard 5 advocates for organisational leadership to develop and maintain systems and processes to deliver patient-centred comprehensive care plans that include appropriate screening to identify and mitigate risks associated with hospitalisation. The aim of this study is to evaluate the effectiveness and cost effectiveness of a comprehensive care and risk evaluation (Comprehensive Assessment and Risk Evaluation (CARE)) plan to reduce hospital acquired complications (HACs) in an Australian hospital network.Methods and analysis This study will comprise a mixed-method pre and post implementation concurrent triangulation evaluation design. The primary clinical outcome will assess the reduction of routinely reported HACs (pressure care and falls), selected based on the likely reliability of routinely collected data prior to implementation. Secondary clinical outcomes will include length of stay and activity-based costing data for each episode, in-hospital mortality, expected and unplanned readmissions within 28 days, compliance with CARE plan completion and referrals for at risk patients, staff satisfaction, patient satisfaction and barriers and enablers to implementation. We expect that the incidence of other HACs (malnutrition, delirium, violence and aggression, and suicide and self-harm) may increase as routine methods for assessing risk were not in place prior to implementation of the CARE plan. We will therefore collect data on incidence of these HACs as tertiary outcomes. Our primary cost-effectiveness outcome will be calculation of an incremental cost-effectiveness ratio.Ethics and dissemination Ethics approval has been received from Northern Health Low Risk Ethics Committee. The results of this study will be published in peer-reviewed journals and presented at conferences.